Évaluation des valeurs d’usage indirect des récifs coralliens et écosystèmes associés de Mayotte - Ewan Trégarot; Pierre Failler; Cindy C. Cornet; Jean-Philippe Maréchal (VertigO, 2020)
Mayotte’s coral reefs (342 km2), mangroves (8, 46 km2) and seagrass beds (7,60 km2) provide important ecosystem services of which the most important are the coastal protection, carbon sequestration, water purification and fish biomass production. The quantity and quality of these services have been decreasing steadily for several years and should continue to do so if no action is taken to contain anthropogenic pressures. The coral cover of the fringing reefs and the barrier reef has thus declined respectively by 60 % in 15 years and 15 % in 8 years, while the pioneer front of Sonneratia for mangroves has declined by 13 % in 6 years. As for the water quality, it suggests a degraded state of seagrass beds. The estimated annual value of these services amounts to EUR 151 million. This value would then rise to EUR 188 million if the ecosystems were in pristine conditions. This article shows that the preservation of coastal ecosystems is essential from an economic point of view.